2020
DOI: 10.2147/prbm.s288983
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Unpredictable Mild Stress Accelerates the Growth of Bladder Cancer in a Xenograft Mouse Model

Abstract: Objective Chronic psychological stress is common in patients with bladder cancer. An increasing number of evidence demonstrated that psychiatric disorder leads to worse prognostic outcomes in bladder cancer. This study was to investigate the effects of chronic psychological stress on the growth of bladder cancer and its potential mechanisms. Methods A xenograft mouse model was established by subcutaneously implanting the human bladder cancer cell line T24 into nude mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Experimental studies found that the combination of social interactions and cognitive stimulation regulated serum in ammatory factors, intestinal mucosal in ammatory factors and hypothalamic ghrelin levels 22,23 . Some TCM herbal medicine, for example, Xiaoyaosan was found to be effective on preventing cancer cell progression and ameliorating gut dysbiosis through CRC mice model with chronic stress 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies found that the combination of social interactions and cognitive stimulation regulated serum in ammatory factors, intestinal mucosal in ammatory factors and hypothalamic ghrelin levels 22,23 . Some TCM herbal medicine, for example, Xiaoyaosan was found to be effective on preventing cancer cell progression and ameliorating gut dysbiosis through CRC mice model with chronic stress 24 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Our team proved the association between the growth of bladder cancer and chronic psychological stress in a nude mouse model. 12 Therefore, we designed a prospective investigation based on previous animal experiments to identify the psychological condition of patients and followed up on the prognosis of patients to analyze the impact of depressive and anxiety symptoms on the prognosis of NMIBC patients.…”
mentioning
confidence: 99%